Factors Associated with the Incidence of Anemia in Toddlers at RS Dera As-Syifa Banjarharjo - Felawati, Ela; Nurhasanah, Nurhasanah; Ratnasari, Eka (Jurnal Medisci, 2023)
The incidence of anemia is a global problem that occurs in developed and developing countries that can have an impact on health, social and economic. Based on data from the World Health Organization (WHO) estimates that 42% of children under 5 years and 40% of pregnant women in the world suffer from anemia. The increased incidence of anemia of toddlers can be caused by the nutritional needs of toddlers more during the growth period. Toddlers who have anemia can have an impact on their immune system and intellectual abilities. The purpose of this study was to determine the factors associated with the incidence of anemia in toddlers at Dera As-Syifa Hospital Banjarharjo Brebes in 2023. This study design used analytical observational research with a cross sectional approach. The sampling technique in this study used a total sampling of 30 people. The results showed that based on the results of the spearman test, a p-value of 0.00 < 0.05 was obtained, which means that there is a relationship between birth weight, parents' economic status and maternal knowledge with the incidence of anemia in toddlers at Dera As-syifa Hospital Banjarharjo Brebes. The conclusion of this study is that there is a relationship between birth weight, parents' economic status and maternal knowledge with the incidence of anemia in toddlers at Dera As-syifa Hospital Banjarharjo.